2015
DOI: 10.1016/j.jped.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Application of tactile/kinesthetic stimulation in preterm infants: a systematic review

Abstract: These studies made a relevant contribution towards indicating tactile/kinesthetic stimulation as a promising tool. Nevertheless, there was no standard for application among them. Future studies should raise the level of methodological rigor and describe the adverse events. This may permit other researchers to be more aware of expected outcomes, and a standard technique could be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 40 publications
0
7
0
4
Order By: Relevance
“…The authors have stated that massage might increase basal metabolism and nutrient absorption through endocrine effects such as increase in insulin and adrenaline and decrease in cortisol. 10,15 In this study, combined effect of improved oral motor control and better neuro-behavioural organization after intervention in experimental group, has enhanced oral motor abilities, with the improved gastric mobility leading to weight gain in infants.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The authors have stated that massage might increase basal metabolism and nutrient absorption through endocrine effects such as increase in insulin and adrenaline and decrease in cortisol. 10,15 In this study, combined effect of improved oral motor control and better neuro-behavioural organization after intervention in experimental group, has enhanced oral motor abilities, with the improved gastric mobility leading to weight gain in infants.…”
Section: Discussionmentioning
confidence: 75%
“…9 In another study on the review on the effects of tactile and kinesthetic stimulation on trunk and extremities on neonatal development in the premature infant, infants receiving massage therapy observed to be receiving greater amount of formula intake (p<0.025) and thus requiring less number of feedings, with early weight gain. 10 When Bertoncelli N et al and others review the effect of sensorimotor stimulation with oral stimulation, the review found that oral and non-oral sensorimotor interventions, provided in combination demonstrated more advanced nutritive sucking, suck-swallow and swallow-respiration coordination than those who received an oral or sensorimotor intervention singly. 11 Similarly the infants in experimental group in the present study received the fixed oral motor intervention protocol i.e., PIOMI with structured M technique protocol, have shown early achievement of full feeds as compared to control group which received only PIOMI.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, cortisol level of their saliva was lower than the other groups (14). As for the positive effects of massage, it can be stated that it helps infants to have a better sleep pattern, lower tension, reduced fluctuations of body temperature, and improved relationship with parents along with weight gaining (15)(16)(17)(18). On the other hand, there are different studies indicating that due to increasing vagus activity, extension and flexion exercises may lead to increased digestive activities and secretion soars of hormones such as insulin, which affects food intake and consequently weight gain (19).…”
Section: Introductionmentioning
confidence: 96%
“…Adicionalmente, se encuentra reportada en la literatura la estimulación kinestésica, la cual consiste en la aplicación de movimientos articulares pasivos y la facilitación de movimientos espontáneos dentro de los rangos normales de movimiento, que permiten el desarrollo de habilidades motoras en los niños prematuros 6,28 ; todo esto debido a que las vías motoras que forman los tractos corticoespinales y la mielinización dependen de la actividad metabólica que se estimula con el movimiento 29 . Los criterios para poder realizar la estimulación kinestésica son similares al de otras maniobras como el masaje, con la excepción de que los estudios recomiendan realizar la técnica 30 a 60 minutos después de la alimentación, para así lograr una adecuada digestión y evitar reflujo gástrico 28,30 . Finalmente, en neonatos con sospecha de lesión cerebral, la estimulación debe ser realizada por un experto, con la cabeza en posición neutral y con una elevación de 30° durante la intervención para prevenir aumento de la presión intracraneana 31 .…”
Section: Introductionunclassified